Wild chimpanzees select tool material based on efficiency and knowledge. Issue 1888 (10th October 2018) - Lamon, Noemie; Neumann, Christof; Gier, Jennifer; Zuberbühler, Klaus; Gruber, Thibaud
Abstract : Some animals have basic culture, but to date there is not much evidence that cultural traits evolve as part of a cumulative process as seen in humans. This may be due to limits in animal physical cognition, such as an inability to compare the efficiency of a novel behavioural innovation with an already existing tradition. We investigated this possibility with a study on a natural tool innovation in wild chimpanzees: moss-sponging, which recently emerged in some individuals to extract mineral-rich liquids at a natural clay-pit. The behaviour probably arose as a variant of leaf-sponging, a tool technique seen in all studied chimpanzee communities. We found that moss-sponges not only absorbed more liquid but were manufactured and used more rapidly than leaf-sponges, suggesting a functional improvement. To investigate whether chimpanzees understood the advantage of moss- over leaf-sponges, we experimentally offered small amounts of rainwater in an artificial cavity of a portable log, together with both sponge materials, moss and leaves. We found that established moss-spongers (having used both leaves and moss to make sponges) preferred moss to prepare a sponge to access the rainwater, whereas leaf-spongers (never observed using moss) preferred leaves. Survey data finally demonstrated that moss was common in forest areas near clay-pits but nearly absent in other forest areas, suggesting that natural moss-sponging was at least partly constrained by ecology. Together, these results suggest that chimpanzees perceive functional improvements in tool quality, a crucial prerequisite for cumulative culture.